Nearly Monodispersed LiNbO3 Nanocrystals Synthesized by a Nonaqueous Sol–Gel Process and Their Photocatalytic H2 Evolution Activities. Issue 24 (26th June 2013) - Feng, Jianyong; Wang, Zhiqiang; Wang, Jiajia; Wan, Lijuan; Yan, Shicheng; Li, Zhaosheng; Zou, Zhigang
Abstract: Phase‐pure and nearly monodispersed LiNbO3 nanocrystals are obtained by a nonaqueous sol–gel process, in which the reaction degrees of the precursors [LiNO3 and Nb(OEt)5 ] are precisely controlled to match each other. The concentration of hydrogen‐related defects affects the H2 evolution activities of the LiNbO3 nanocrystals. Abstract : The synthesis of phase‐pure multimetal oxides in a nonaqueous sol–gel system requires equal reaction rates of the different precursors. In this study, the reaction degrees of mismatched precursors, LiNO3 and Nb(OEt)5, are tuned to match each other, and as a result nearly monodispersed phase‐pure LiNbO3 nanocrystals are obtained.